2018
DOI: 10.3329/ajmbr.v4i3.38467
|View full text |Cite
|
Sign up to set email alerts
|

Identification and antibiogram study of bacteria isolated from different street food

Abstract: Food borne diseases are an increasingly recognized problem involving a wide spectrum of illnesses caused by bacterial contamination of food.Microorganism poses potential human health problems and is mainly transmitted through consumption of contaminated foods .Bangladesh is one of the densely populated country where majority of the people consume cheap foods prepared in unlicensed food selling points. The objective of the present study was to investigate the microbiological quality of different street food (Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…These results are consistent with an Egyptian study in Luxor city which found that the isolation rate of Salmonella in ready-to-eat meat (RTE) samples was 6.67% (Younis et al ., 2019). However, a slightly lower rates were reported in Bangladesh (5%) and in Egypt (4.4%) where Salmonella prevalence in street food was 5 % (Abd- El–Malek, 2017; Khalif et al ., 2018). In contrast, higher rates where reported from Korea (22.4%), Australia (38.8%), and China (54%) (Kim et al ., 2012; Fearnley et al ., 2011; Yang et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with an Egyptian study in Luxor city which found that the isolation rate of Salmonella in ready-to-eat meat (RTE) samples was 6.67% (Younis et al ., 2019). However, a slightly lower rates were reported in Bangladesh (5%) and in Egypt (4.4%) where Salmonella prevalence in street food was 5 % (Abd- El–Malek, 2017; Khalif et al ., 2018). In contrast, higher rates where reported from Korea (22.4%), Australia (38.8%), and China (54%) (Kim et al ., 2012; Fearnley et al ., 2011; Yang et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Street food is defined as the type of food and beverages that are prepared or sold by street vendors in public areas for human consumption, with or without the need for additional processing and preparation [ 1 3 ]. It is an important business that helps developing nations meet the food needs of the poor [ 4 ] and promote socioeconomic development by providing employment for many unemployed people [ 2 , 5 , 6 ]. Besides, they attract tourists in some Asian countries [ 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lack of training on proper food handling and processing, poor personal hygiene of vendors, and unsanitary surroundings could all be contributing factors to the observed safety issues [ 2 , 4 ], which often lead to the rise of various food-borne diseases that can be life-threatening [ 3 ]. The issue is most pronounced in countries with insufficient food safety laws, weak regulatory systems, limited financial resources for safer equipment, and food safety training [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Street food refers to food and drinks that are prepared and sold by fast vendors or retailers, typically on the spot or in the same public place, for local consumption or later consumption without further preparation [1]. Vendors or manufacturers usually prepare street food in mobile food carts or food trucks, and it is intended to be consumed by customers.…”
Section: Introductionmentioning
confidence: 99%